Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase

Structure of highly active BSH enzyme with subordinated post-translational excision - Chand, Deepak; Panigrahi, Priyabrata; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Bile salt hydrolase; Mutagenesis; X-ray crystallography

Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C. G. (Journal of Industrial Microbiology & Biotechnology, 2015)
Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in beta-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans (PdPGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted PdPGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans. Experimental data showed that PdPGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, PdPGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in PdPGA, which upon mutation selectively could improve the thermostability of the enzyme.
Keywords: Alkalistable; beta-lactam antibiotics; Consensus approach; Disulfide bridge; Ion pairs; Penicillin acylase; Thermostability

Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase

Structural analysis of a penicillin V acylase from pectobacterium atrosepticum confirms the importance of two Trp residues for activity and specificity - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Chand, Deepak; Pundle, Archana; Suresh, Cheravakattu Gopalan; Ramasamy, Sureshkumar (Journal of Structural Biology, 2016)
Penicillin V acylases (PVA) catalyze the deacylation of the beta-lactam antibiotic phenoxymethylpenicillin (Pen V). They are members of the Ntn hydrolase family and possess an N-terminal cysteine as the main catalytic nucleophile residue. They form the evolutionarily related cholylglycine hydrolase (CGH) group which includes bile salt hydrolases (BSH) responsible for bile deconjugation. Even though a few PVA and BSH structures have been reported, no structure of a functional PVA from Gram-negative bacteria is available. Here, we report the crystal structure of a highly active PVA from Gram-negative Pectobacterium atrosepticum (PaPVA) at 2.5 angstrom resolution. Structural comparison with PVAs from Gram-positive bacteria revealed that PaPVA had a distinctive tetrameric structure and active site organization. In addition, mutagenesis of key active site residues and biochemical characterization of the resultant variants elucidated the role of these residues in substrate binding and catalysis. The importance of residue Trp23 and Trp87 side chains in binding and correct positioning of Pen V by PVAs was confirmed using mutagenesis and substrate docking with a 15 ns molecular dynamics simulation. These results establish the unique nature of Gram-negative CGHs and necessitate further research about their substrate spectrum. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Aromatic stacking; Cholylglycine hydrolase; molecular dynamics; Mutagenesis; Oligomeric interactions